Identification of Putative Substrates for the Periplasmic Chaperone YfgM in Escherichia coli Using Quantitative Proteomics - Götzke, Hansjörg (Mol Cell Proteomics, 2015)
How proteins are trafficked, folded, and assembled into functional units in the cell envelope of Gram-negative bacteria is of significant interest. A number of chaperones have been identified, however, the molecular roles of these chaperones are often enigmatic because it has been challenging to assign substrates. Recently we discovered a novel periplasmic chaperone, called YfgM, which associates with PpiD and the SecYEG translocon and operates in a network that contains Skp and SurA. The aim of the study presented here was to identify putative substrates of YfgM. We reasoned that substrates would be incorrectly folded or trafficked when YfgM was absent from the cell, and thus more prone to proteolysis (the loss-of-function rationale). We therefore used a comparative proteomic approach to identify cell envelope proteins that were lower in abundance in a strain lacking yfgM, and strains lacking yfgM together with either skp or surA. Sixteen putative substrates were identified. The list contained nine inner membrane proteins (CusS, EvgS, MalF, OsmC, TdcB, TdcC, WrbA, YfhB, and YtfH) and seven periplasmic proteins (HdeA, HdeB, AnsB, Ggt, MalE, YcgK, and YnjE), but it did not include any lipoproteins or outer membrane proteins. Significantly, AnsB (an asparaginase) and HdeB (a protein involved in the acid stress response), were lower in abundance in all three strains lacking yfgM. For both genes, we ruled out the possibility that they were transcriptionally down-regulated, so it is highly likely that the corresponding proteins are misfolded/mistargeted and turned-over in the absence of YfgM. For HdeB we validated this conclusion in a pulse-chase experiment. The identification of HdeB and other cell envelope proteins as potential substrates will be a valuable resource for follow-up experiments that aim to delineate molecular the function of YfgM.